The effects of soaking and physical treatments to the purine content of Mung Beans (Vigna radiata) - Seduco, Noriel Antivo (2016.)
Purines are nitrogenous bases composing the nucleotides of the DNA and RNA of the cells and its breakdown in the body leads to the production of uric acid. The production of uric acid is a normal metabolic process but can lead to a condition called hyperuricemia in elevated levels. Furthermore, the accumulation of uric acid crystals in some parts of the body can lead to a disorder called gouty arthritis. Foods which contain moderate to high purines include mung beans (Vigna radiata). Mung bean is one of the most common food source in most part of the world including the Philippines. However, little has been known about how some soaking and physical treatments of mung bean seeds affect its purine content. This study aimed to determine the effects of soaking and physical treatments to the purine content of mung beans. Mung bean samples were soaked and physically treated. The purine content was then isolated by acid hydrolysis using perchloric acid. It was subsequently followed by precipitation with AgNO3. Purines were then relatively quantified relatively using the murexide test and absorbance were read at 506 nm. Results showed that all the treatments employed significantly lowered the purine content of mung beans with p = 0.001. Specifically, this study found out that the longer the time of soaking of mung beans, the lower is its purine content. Soaking treatment for 72 hours had the lowest absorbance with 0.012 ± 0.003. Coarse-grinding of the mung beans also lowered the purine content. On the other hand, cold temperature storage had a lesser tendency to lower the purine content of the mung beans.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Mung Beans, Vigna radiata; Purines; Uric acid; Soaking